Pit Viper Venom-Induced Coagulopathy: Mandatory Antivenom, Avoidance of Anticoagulants, and Selective Transfusion - Indrayani, Made; Andriyasa, I Ketut; Nugraha, Putu Arya; Widiastika, Made; Kluniari, Ni Made Nova Andari (Syntax Literate, 2025)
Venom-induced consumption coagulopathy (VICC) is a life-threatening complication following pit viper bites and remains a significant health concern in Southeast Asia. VICC has a distinct pathophysiology compared to typical disseminated intravascular coagulation (DIC), requiring a tailored management approach. This case highlights the successful treatment of severe VICC following a red-tailed green viper bite. A 64-year-old woman presented with left hand swelling three days after a red-tailed green viper bite to the wrist. She also had vomiting and fever on first day. She was alert and hemodynamically stable. Laboratory tests revealed severe thrombocytopenia (50 x 10³/μL), markedly elevated D-dimer (>10,000 ng/mL), and prolonged coagulation times. Complications included acute kidney injury, elevated liver enzymes, and gross hematuria. She received an initial dose of 2 vials of antivenom with close monitoring. As her coagulopathy progressed, additional antivenom was administered every 8 hours. Her condition began improving on day five without requiring blood transfusion. Unlike typical DIC, VICC should be managed primarily with antivenom, which neutralizes circulating venom and halts further coagulopathy. Anticoagulants are contraindicated, as pit viper venom contains both procoagulant and anticoagulant components that can worsen bleeding. The use of blood products in VICC is selective and symptom-based. Fresh frozen plasma (FFP) may be considered in patients with active bleeding or severe coagulopathy, thrombocyte concentrate (TC) is indicated if thrombocytopenia persists despite adequate antivenom, and packed red cells (PRC) are reserved for life-threatening anemia. VICC is a distinct coagulopathy requiring prompt antivenom administration, careful avoidance of anticoagulants, and judicious use of transfusions.